TINGKAT PEMAHAMAN TOLERANSI PADA MAHASISWA UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Anisa Fitriani; Alfa Ilmiyatun Nafiah; Annafi Ainiyyah; Achmad Tubagus Surur (JOURNAL SAINS STUDENT RESEARCH, 2025)
Era Z could be a era that developed up within the middle of innovative improvements and within the time of digitalization, as well as cultural, religious, and life outlook diversity. In this context, an attitude of tolerance is very necessary to maintain harmony. The family environment and education can play a role in fostering an attitude of tolerance. In addition, openness to differences, critical discussions, and direct experience with diversity are factors in fostering an attitude of tolerance.